Suzuki–Miyaura Coupling of Aryl Sulfonates with Arylboronic Acids Using a Morpholine–Pd(OAc)2 Catalyst System. Issue 18 (13th May 2014) - Abe, Taichi; Mino, Takashi; Watanabe, Kohei; Yagishita, Fumitoshi; Sakamoto, Masami
Abstract: We report a new catalyst system, a morpholine–Pd(OAc)2 complex, for Suzuki–Miyaura coupling of aryl tosylates or mesylates with arylboronic acids to give biaryl compounds. The morpholine–Pd(OAc)2 catalyst system is proposed to be a precursor of the catalytically active species in the coupling reaction. Aryl chlorides and aryl triflates can also be used in this coupling reaction. Altogether, 22 biaryl compounds were obtained using this catalyst system. Abstract : We report a new catalyst system, a morpholine–Pd(OAc)2 complex, for Suzuki–Miyaura coupling of aryl tosylates or mesylates with arylboronic acids to give biaryl compounds. The morpholine–Pd(OAc)2 catalyst system is proposed to be a precursor of the catalytically active species in the coupling reaction.